Maternity leave legislation, female labor supply, and the family wage gap - Uta Schönberg; Johannes Ludsteck (Institute for the Study of Labor (IZA), 2007)
This paper analyzes the impact of expansions in leave coverage on mothers' labor market outcomes after childbirth. The focus is on Germany, a country that underwent several changes in maternity leave legislation since the late 70s. We identify the causal impact of an expansion in maternity leave by comparing labor market outcomes of women who gave birth shortly (i.e. one month) before and after a change in maternity leave legislation. There is strong evidence that each expansion induced women to delay their return to work. Despite this strong short-term effect, the expansions had little impact on women's labor supply in the long-run. The expansion from 2 to 6 months reduced women's wages, even 8 years after childbirth. This effect is mostly explained by the delay in the return to work. The delay in the return to work caused by the expansions in leave from 6 to 10 months and 18 to 36 months also lowered wages. However, this negative effect is offset by a positive selection effect, resulting in a zero or even positive overall effect.
urn:nbn:de:101:1-20080410188
Keywords: 330; Erziehungsurlaub; Frauenerwerbstätigkeit; Lohndrift; Lohndifferenzierung; Frauenarbeitslohn; Deutschland